Ill met by murder - Duncan, Elizabeth J. (Duncan, Elizabeth J. Shakespeare in the Catskills mysteries., 2016)
When a family friend of the theater company's wealthy benefactor is found murdered shortly before the wedding of the benefactor's daughter, costume designer Charlotte Fairfax decides she must investigate.